MiR-142-3p attenuates the migration of CD4⁺ T cells through regulating actin cytoskeleton via RAC1 and ROCK2 in arteriosclerosis obliterans. - Jiawei Liu (PLoS ONE, 2014)
The migration of CD4+ T cells plays an important role in arteriosclerosis obliterans (ASO). However, the molecular mechanisms involved in CD4+ T cell migration are still unclear. The current study is aimed to determine the expression change of miR-142-3p in CD4+ T cells from patients with ASO and investigate its role in CD4+ T cell migration as well the potential mechanisms involved. We identified by qRT-PCR and in situ hybridization that the expression of miR-142-3p in CD4+ T cells was significantly down-regulated in patients with ASO. Chemokine (C-X-C motif) ligand 12 (CXCL12), a common inflammatory chemokine under the ASO condition, was able to down-regulate the expression of miR-142-3p in cultured CD4+ T cells. Up-regulation of miR-142-3p by lentivirus-mediated gene transfer had a strong inhibitory effect on CD4+ T cell migration both in cultured human cells in vitro and in mouse aortas and spleens in vivo. RAC1 and ROCK2 were identified to be the direct target genes in human CD4+ T cells, which are further confirmed by dual luciferase assay. MiR-142-3p had strong regulatory effects on actin cytoskeleton as shown by the actin staining in CD4+ T cells. The results suggest that the expression of miR-142-3p is down-regulated in CD4+ T cells from patients with ASO. The down-regulation of miR-142-3p could increase the migration of CD4+ T cells to the vascular walls by regulation of actin cytoskeleton via its target genes, RAC1 and ROCK2.